2020
DOI: 10.1101/2020.10.30.20223149
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Availability of personal protective equipment and satisfaction of healthcare professionals during COVID-19 pandemic in Ethiopia

Abstract: Healthcare professionals (HCPs) are at the frontline in the fight against COVID-19 and are at an increased risk of becoming infected with coronavirus. Risk of infection can be minimized by use of proper personal protective equipment (PPE). This study assessed the availability of PPE and satisfaction of HCPs in six public hospitals in Addis Ababa, Ethiopia. A cross-sectional study was conducted from 9th to 26th June 2020. The study hospitals included: Tikur Anbessa Specialized Hospital, Zewditu Memorial Hospita… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…About two-third of the respondents were dissatisfied with the low level of availability of PPDs in their hospital. This finding corroborates with the study in Ethiopia which reported an overall low level of satisfaction of healthcare practitioners with the availability and use of appropriate PPDs in their hospital [20].…”
Section: Discussionsupporting
confidence: 91%
“…About two-third of the respondents were dissatisfied with the low level of availability of PPDs in their hospital. This finding corroborates with the study in Ethiopia which reported an overall low level of satisfaction of healthcare practitioners with the availability and use of appropriate PPDs in their hospital [20].…”
Section: Discussionsupporting
confidence: 91%
“…35 In this study, there was no significant difference between case and control regarding PPE availability this result is different than reported in a cross-sectional study in Ethiopia the study included 1228 HCWs that reported an overall shortage of PPE the majority (77%) of HCWs reported that their hospital did not have adequate PPE. 36 In survey study that was conducted in 33 hospitals in Sudan among workers in all radiology department reported that 75% of all workers had sufficient knowledge about hand hygiene and hand hygiene is embedded in their routine clinical practice. 37 Also, in a cross-sectional study in 13 regions of Saudi Arabia among HCWs in radiology department reported that the majority of radiographic technologists reported wearing the recommended PPE regardless the patient infectious states during this pandemic and 80% of participant received frequent training about infection prevention and control at their health institutions while in this study only 50.8% of participant received training about infection prevention and control practice.…”
Section: Discussionmentioning
confidence: 99%
“…74,76,77 Lack of proper training and guidelines, critical shortage of PPE, lack of scientific evidence at hand, low local support, lack of proper communication and collaboration between stakeholders, and fear of contracting the infection were reported by the HCWs to be the major limiting factors. 39,[74][75][76] Though limited, the studies have clearly depicted that the collateral damage was felt more than the direct impacts of the outbreak during the first few months. Maternal health service utilization declined significantly compared with the previous months.…”
Section: Discussionmentioning
confidence: 99%
“…Major reasons mentioned by HCWs were lack of training, critical shortage of PPE, lack of scientific evidence at hand, inability to access guidelines and recommendations, limited access for literature, low local support, poor communication and collaboration between stakeholders, and fear of contracting the infection. 39,[74][75][76]…”
Section: Preparedness For Covid-19 Controlmentioning
confidence: 99%